2019
DOI: 10.1007/s40264-019-00856-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Nature of Medication Errors and Preventable Adverse Drug Events in Paediatric and Neonatal Intensive Care Settings: A Systematic Review

Abstract: IntroductionChildren admitted to paediatric and neonatal intensive care units may be at high risk from medication errors and preventable adverse drug events.ObjectiveThe objective of this systematic review was to review empirical studies examining the prevalence and nature of medication errors and preventable adverse drug events in paediatric and neonatal intensive care units.Data SourcesSeven electronic databases were searched between January 2000 and March 2019.Study SelectionQuantitative studies that examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 88 publications
3
78
2
6
Order By: Relevance
“…Antimicrobials were the drugs most commonly involved in UDs of children in the three transitions analyzed in this study. Alghamdi et al, (2019) [18] reported that antimicrobials were the drugs most frequently involved in potential adverse events and medication errors. The high rate of antimicrobial use in children can be explained by the high prevalence of infectious diseases in this population [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobials were the drugs most commonly involved in UDs of children in the three transitions analyzed in this study. Alghamdi et al, (2019) [18] reported that antimicrobials were the drugs most frequently involved in potential adverse events and medication errors. The high rate of antimicrobial use in children can be explained by the high prevalence of infectious diseases in this population [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Any discrepancies found between the patients' medication list and prescriptions were classified as follows [18]:…”
Section: Evaluation Of Discrepanciesmentioning
confidence: 99%
“…We identified all children <18 years of age admitted to the pediatric intensive care unit (PICU) or pediatric cardiac intensive care unit (PCICU) at Duke University during a 2year period who were administered midazolam via bolus or continuous infusion to facilitate mechanical ventilation and who had !1 Cornell Assessment of Pediatric Delirium (CAPD) score at any time after the initiation of midazolam. We defined dates of inclusion based on the following changes in institutional protocols: (1) in October 2014, after extensive nursing training, Duke University began screening critically ill children for delirium twice daily per standard of care with the CAPD tool; and (2) a new sedation protocol that limited midazolam use in the PICU. Throughout the entire study period, the PICU maintained a standard protocol for use of the CAPD.…”
Section: Populationmentioning
confidence: 99%
“…Children are especially vulnerable to medication errors, particularly dosing errors resulting from inaccurate weight measurements or incorrect weight-dependent calculations. 1 - 4 Moreover, the emergency department is one area of health care most prone to medication errors in prescribing, transcription, administration, and monitoring. 5 - 7 Studies have identified prescribing errors in 10% to 30% of the charts 8 , 9 and a higher rate of errors among residents with less experience, with an especially high rate of errors at the beginning of the academic year.…”
Section: Introductionmentioning
confidence: 99%